Peningkatan Hasil Belajar Siswa Pada Sistem Persamaan Linear Dua variabel melalui Model Pembelajaran Jigsaw di MTs. Nuruz Zaman Mayang Jember - Heriyanto, Heriyanto (FKIP Universitas Islam Jember, 2020)
The achievement of a science and technology cannot be separated from education. In this study conducted observations in class VIII MTs. Nuruz Zaman Mayang, it was found that they still think that mathematics is not more than just counting and playing with formulas and numbers. To find out the increase in activity and student learning outcomes through the jigsaw learning model on the material of the two-variable linear equation system for class VIII Mts Nuruz Zaman Mayang Jember. The type of research in this research is classroom action research (PTK). This approach uses a qualitative approach and a quantitative approach. The procedure used is a cycle model. Based on the results of the study, the percentage of student learning activities in cycle I experienced classical completeness 79.31% and cycle II (≥85%). This shows that student activity is in good category, because it has a percentage of ≥70% to ≤80%. This proves that the increase in student activity and learning outcomes through the jigsaw learning model on the subject matter of the two-variable linear equation system class VIII Mts Nuruz Zaman